Understanding the cultural identity of EFL learners from the eco-linguistics perspective: evidence from students in arts college before and after the COVID-19 epidemic period - Peng, Yue (Frontiers in Psychology, 2023)
The identity development process has individual and societal components and is inherently intertwined with one’s broader sociocultural milieu. The correlation between the personal and social aspects of an individual’s identity considerably influences their behavior within their environment. This study examines cultural identity changes among English as a Foreign Language (EFL) students by conducting a questionnaire survey based on the anxiety/uncertainty management theory by Gudykunst(1995,1998). The questionnaire was distributed twice: Study 1 used data from 483 students and Study 2 used data from 359 students. After each study, 20 students’ descriptions of Chinese and Western cultures were analyzed in NVivo. Guided by the ecological research paradigm, this study examines the impact of individual differences on cultural identity at the macro-, meso-, exo-, and micro- levels. The findings suggest that social context can influence an individual’s cultural identity, and cultural identity development accompanies being “oneself.”